Balloon measurements of the vertical ionization profile over southern Israel and comparison to mid-latitude observations. (November 2016) - Yaniv, Roy; Yair, Yoav; Price, Colin; Nicoll, Keri; Harrison, Giles; Artamonov, Anton; Usoskin, Ilya
Abstract: Airborne measurements using meteorological balloons were conducted for the first time from southern Israel (geographic 30°35'N, 34°45'E geomagnetic 27°6'N 112°23'E) for measuring the vertical ionization profile during solar cycle 24. The results show the differences (increase of ~30%) in count rates as we proceed from solar maximum toward solar minimum. The observed altitude of maximum ionization (the Regener-Pfotzer maximum) was between 17–20 km, and it agrees well with results from other simultaneous measurements conducted at different latitudes (Reading, UK and Zaragoza-Barcelona, Spain). When compared with predictions of an analytical model, we find a highly significant correlation (R 2 =0.97) between our observations and the computed ionization profiles. The difference in count rates can be attributed to the height of the tropopause due to the model using a US standard atmosphere that differs from the measured atmospheric parameters above Israel. Highlights: First report on the ionization profile above southern Israel from 6 balloon flights conducted 2014–2016. The height of the Regener-Pfotzer maximum is compared with measurements from mid-latitude observations in the UK and Spain and positively matches model predictions. We show an increase in ionization rates along the campaign period, in line with the declining phase of solar cycle 24.